2022
DOI: 10.55251/jmbfs.4224
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Plant Lectins in Biotechnology and Therapeutics

Abstract: Lectins are carbohydrate-binding proteins broadly used in various therapeutic and biomedical applications. The variable affinity of lectins towards variety of carbohydrates has raised attention for the biologist to explore functional aspects of lectins.  Lectins express specificity to simple carbohydrates for example mannose, lactose, sialic acid, complex glycan, and glycoproteins. Lectins are classified based on their sugar specificity and are used as a tool to study protein-carbohydrate interactions. Lectins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Understanding the human glycome comprises a crucial portion of cancer research since targeting cancerrelated glycan structures is quickly emerging as an effective diagnostic method [78][79][80]. In this context, several studies have reported on the use of lectins to map changes in the glycosylation patterns of malignant cells, making it possible to follow and predict the progression of the disease and the degree of malignancy [55,[81][82][83][84][85][86]. To accomplish this, several well-known techniques can be used, including, for example, Enzyme-Linked Lectin Assay (ELLA) [87,88], immunohistochemistry [89][90][91], lectin nanoparticle assays [92], glyco-functionalized quantum dots (QDs) with lectins [93], lectin blot analysis [58,94], lectins conjugated with fluoro-microbeads and antibody-lectin sandwich assay [87,95], SDS-PAGE/Western Blotting [96], and fluorescent labeling techniques [97,98], among others [99][100][101].…”
Section: Lectins As Diagnostic Tools Against Bcamentioning
confidence: 99%
“…Understanding the human glycome comprises a crucial portion of cancer research since targeting cancerrelated glycan structures is quickly emerging as an effective diagnostic method [78][79][80]. In this context, several studies have reported on the use of lectins to map changes in the glycosylation patterns of malignant cells, making it possible to follow and predict the progression of the disease and the degree of malignancy [55,[81][82][83][84][85][86]. To accomplish this, several well-known techniques can be used, including, for example, Enzyme-Linked Lectin Assay (ELLA) [87,88], immunohistochemistry [89][90][91], lectin nanoparticle assays [92], glyco-functionalized quantum dots (QDs) with lectins [93], lectin blot analysis [58,94], lectins conjugated with fluoro-microbeads and antibody-lectin sandwich assay [87,95], SDS-PAGE/Western Blotting [96], and fluorescent labeling techniques [97,98], among others [99][100][101].…”
Section: Lectins As Diagnostic Tools Against Bcamentioning
confidence: 99%